sRAGE Is Elevated in the Lungs of Premature Infants Receiving Mechanical Ventilation - Rozycki, Henry J.; Bradley, Jennifer; Karam, Simon (American Journal of Perinatology, 2017)
Background Soluble receptor for advanced glycation end-products (sRAGE), a soluble isoform of the RAGE receptor, is elevated in lungs from patients with acute conditions such as acute respiratory distress syndrome and bronchiolitis. This study investigated whether sRAGE is present in ventilated infants.Methods Tracheal aspirates from the first week or the fifth week of life were obtained from intubated very low birth weight subjects and analyzed by Western blot. Immunohistochemistry analysis for sRAGE was performed on paraffin-embedded lung autopsy slides from 19 other infants.Results The sRAGE band densities were similar among the seven infants who fully recovered, eight who developed bronchopulmonary dysplasia (BPD), and 5 who died (analysis of variance p = 0.797) but was higher at 4 weeks, p = 0.0324. There was minimal sRAGE staining in the autopsied lungs from previable infants (20–21 weeks) or from those who were not ventilated or had mild lung disease. In contrast, substantial staining was present in two of three with BPD, and those who received high ventilatory support.Conclusion sRAGE is present in ventilated infants. Levels are generally higher in those who receive prolonged or vigorous mechanical ventilation. Since sRAGE may have roles in inflammation and cell adherence, its role in the development of BPD may warrant study.
Keywords: very low birth weight; biomarker; bronchopulmonary dysplasia; lung injury